2016
DOI: 10.3390/ma9121001
|View full text |Cite
|
Sign up to set email alerts
|

The Refining Mechanism of Super Gravity on the Solidification Structure of Al-Cu Alloys

Abstract: There is far less study of the refining effect of super gravity fields on solidification structures of metals than of the effects of electrical currents, magnetic and ultrasonic fields. Moreover, the refining mechanisms of super gravity are far from clear. This study applied a super gravity field to Al-Cu alloys to investigate its effect on refining their structures and the mechanism of interaction. The experimental results showed that the solidification structure of Al-Cu alloys can be greatly refined by a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Considering the fact that the most remarkable characteristic is that super-gravity can significantly promote the relative motion between solid-liquid, gas-liquid and liquid-liquid because of the difference in density. [27][28][29][30][31][32][33] What's more, our previous study 24) reported that the "crystal rain" caused by super-gravity was contributed to the mechanism of the grain refinement of Al-Cu alloys. Therefore, it is expected that a similar mechanism is occurring in super-gravity field as a result of the moving behavior of crystal nuclei.…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation
“…Considering the fact that the most remarkable characteristic is that super-gravity can significantly promote the relative motion between solid-liquid, gas-liquid and liquid-liquid because of the difference in density. [27][28][29][30][31][32][33] What's more, our previous study 24) reported that the "crystal rain" caused by super-gravity was contributed to the mechanism of the grain refinement of Al-Cu alloys. Therefore, it is expected that a similar mechanism is occurring in super-gravity field as a result of the moving behavior of crystal nuclei.…”
Section: Figmentioning
confidence: 94%
“…Wu's simulation study did not take account of the movement of equiaxed grains, which can markedly influence the solidification structure of castings. 22,23) Also, the solidification structure refinement of Al-Cu alloys in super-gravity field has been investigated systematically in our recent study, 24) which demonstrated that the "crystal rain" caused by super-gravity contributed to the grain refinement.…”
Section: Effect Of Super-gravity Field On Grain Refinement and Tensilmentioning
confidence: 99%
“…So, in this research, it is believed that the atom cluster mechanism does not play the leading role. For the effect of solid movement on the macrosegregation, our previous study [11] analyzed the crystal's moving behavior in super gravity field: for low-concentrated Al-Cu alloys, the solid settled down, which should result in negative segregation at the bottom of the sample, and for high-concentrated Al-Cu alloys, the solid floated upward, which should result in positive segregation at the bottom of the sample. However, according to the present experimental results, the solute Cu always segregated toward the bottom of the sample for all the Al-Cu alloys.…”
Section: Gravity Segregation Mechanismmentioning
confidence: 99%
“…As one of the external physical fields, super gravity field has presented great advantage at the fabrication of functionally graded materials [1][2][3], metal purification [4][5][6] and recovery of valuable resources [7][8][9] using its great intensification effect of relative movement [10]. A number of researches have investigated the solidification structure evolution of metals in super gravity field [11][12][13][14][15]. However, the segregation phenomenon of solute element was also found and it is unavoidable in centrifugal casting process.…”
Section: Introductionmentioning
confidence: 99%
“…The application of the high magnetic field suggested a possibility of adjusting the morphology of solid-liquid phase during the solidification of Al-Cu alloys [8], which shows a potential way to control the distribution and amount of porosities. Previous research [1,2] found that the application of the magnetic field can cause grain refinement, in which some of the resulting microstructures are much better than those used by other solidification technology, for example, supergravity solidification [9]. Zuo et al [10] pointed out that the increasing external magnetic field can tilt the growth direction of the lamellar eutectic and decrease the coarse eutectic lamellar spacing during solidification, leading to a higher strength.…”
Section: Introductionmentioning
confidence: 99%